Experimental investigation on mechanical properties of flax/banana/ industrial waste tea leaf fiber reinforced hybrid polymer composites. (2021) - Prabhu, L.; Krishnaraj, V.; Sathish, S.; Gokulkumar, S.; Karthi, N.; Rajeshkumar, L.; Balaji, D.; Vigneshkumar, N.; Elango, K.S.; Karpagam, J.; Vijayalakshmi, V.J.; Gowarthan, E.R.; et al.
Abstract: In the present research, work focus has been given to determine mechanical properties of biodegradable industrial waste tea leaf fiber (WTLF), banana and flax fiber reinforced hybrid polymer composites using experimental approach. Banana fibers and WTLF were alkali treated with 5% NaOH solution. The hybrid composite laminates were manufactured using manually operated compression moulding machine with the volume fraction of 40:60 (Fiber: Matrix). As per ASTM standard, the mechanical characteristics were studied. The experimental results showed excellent mechanical characteristics for 5 wt% WTLF and 25- wt% banana fiber reinforced hybrid composites. The fractography analysis of untreated and alkali treated composites were examined using Scanning Electron Microscopy (SEM) and results revealed that superior mechanical bonding existed between fiber and polymer in case of alkali treated fiber composites.